The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1001/jamacardio.2019.1384
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Ambulatory Hemodynamic Monitoring of Heart Failure With Clinical Outcomes in a Concurrent Matched Cohort Analysis

Abstract: IMPORTANCE In a randomized clinical trial, heart failure (HF) hospitalizations were lower in patients managed with guidance from an implantable pulmonary artery pressure sensor compared with usual care. It remains unclear if ambulatory monitoring could also improve long-term clinical outcomes in real-world practice. OBJECTIVE To determine the association between ambulatory hemodynamic monitoring and rates of HF hospitalization at 12 months in clinical practice. DESIGN, SETTING, AND PARTICIPANTS This matched co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Additional analyses in a subset of 480 patients showed a risk reduction of 34% (HR 0.66, 95% CI 0.57–0.76) after 12 months of follow-up [ 26 ]. Another cohort study used the Medicare claims database to identify 1087 CardioMEMS patients and matched these patients to 1087 control patients by using the propensity score technique [ 27 ]. A significant difference in HF hospitalization rates was found in favor of the CardioMEMS cohort at 12 months post-implant (HR 0.76, 95% CI 0.65–0.89).…”
Section: Pulmonary Artery Pressure Sensorsmentioning
confidence: 99%
“…Additional analyses in a subset of 480 patients showed a risk reduction of 34% (HR 0.66, 95% CI 0.57–0.76) after 12 months of follow-up [ 26 ]. Another cohort study used the Medicare claims database to identify 1087 CardioMEMS patients and matched these patients to 1087 control patients by using the propensity score technique [ 27 ]. A significant difference in HF hospitalization rates was found in favor of the CardioMEMS cohort at 12 months post-implant (HR 0.76, 95% CI 0.65–0.89).…”
Section: Pulmonary Artery Pressure Sensorsmentioning
confidence: 99%
“…CardioMEMS is the only invasive heart failure (HF) remote monitoring sensor with Food and Drug Administration (FDA) approval and European Conformity (CE) mark. The CardioMEMS HF system is recommended in the European Society of Cardiology (ESC) guidelines of 2016 with a class II b level B recommendation, which is expected to be upgraded in the newest version of the guidelines in 2021 with evidence from several new studies [1,[6][7][8][9][10]. The CardioMEMS PA sensor has no internal power supply and is fully compatible with implantable cardioverter defibrillators (ICDs), (cardiac resynchronization therapy) CRT devices and left ventricular assist devices (LVADs).…”
Section: The Cardiomems Hf Systemmentioning
confidence: 99%
“…Several studies have examined the effectiveness of ambulatory hemodynamic monitoring by the CardioMEMS HF system in reducing HF hospitalization outside strict clinical trials or prospective study settings [ 9 , 10 ]. Desai et al conducted a retrospective cohort study using 1114 patients from the U.S. Medicare claims database who had a CardioMEMS sensor implanted between 1 June 2014 and 31 December 2015 [ 9 ].…”
Section: Open-access Extension Of the Champion Trialmentioning
confidence: 99%
“…23 Subsequent real-world data in thousands of patients demonstrate similar outcomes to those reported in the CHAMPION pivotal trial. [24][25][26] Most recently, large propensity matched analyses in real-world cohorts found that haemodynamically monitored patients with HF had significant reductions in days lost due to death or hospitalization, with associative improved survival in the monitored group. 26 Haemodynamic guided HF management with remote PA pressure monitoring, however, was predominantly tested in the United States healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Most recently, large propensity matched analyses in real-world cohorts found that haemodynamically monitored patients with HF had significant reductions in days lost due to death or hospitalization, with associative improved survival in the monitored group. 26 Haemodynamic guided HF management with remote PA pressure monitoring, however, was predominantly tested in the United States healthcare system. The PA pressure monitoring system (CardioMEMS TM HF System, Abbott, Atlanta, GA, USA) has the CE mark and Therapeutic Goods Administration approval and is modelled to possibly be cost-effective in other geographies.…”
Section: Introductionmentioning
confidence: 99%